Polymerization on the lactide to PLA the effect of lactide concentration / Mohd Aizat Zamri - Zamri, Mohd Aizat (2019)
Polylactide was synthesized via ring –opening polymerization of lactide. The ring opening polymerization of lactide usually used the homogenous catalyst for the process polymerization of the lactide. But, for the polymerization process used the homogenous catalyst need the complex separation process in liquid-liquid component. Then, the heterogeneous catalyst need to use so the process of separation of PLA more easy. The tin octoace was used as the catalyst for this experiment. The aim of this experiment to study the polymerization of lactide with the heterogeneous catalyst. The properties of PLA were studied as a function of the concentration of lactide (0.5M, 0.3 and 0.1M) relative to the synthesis of PLA. The PLA were characterize by uv-visible spectroscopy (UV-vis) and Fourier transform infrared spectroscopy (FT-IR). The UV-vis showed the wavelength 233 nm of the PLA in the solution with different absorbance. FT-IR spectra showed the different between PLA and the lactide.